Making Web-Based Product And Inventory Applications Using The Laravel Framework (Case Study : Cv. Global Best Ls) - Rakan Lawahiz Zhafran Ferial Faiz Al Laitsi (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2022)
The process of recording the inflow and outflow of goods is an important process in the company's inventory system. However, often this recording process is not noticed by the company and instead allows the manual process to continue. This results in frequent errors in the recording of goods made in writing. Through a technological approach such as the use of applications in companies, records can start to be computerized as the development of the existing system. This study aims to create a product and inventory application with the First In First Out (FIFO) method as the flow of goods filtration. One method approach in application design is Rapid Application Development (RAD) which is a method with feedback that helps in completing application features. By working using the laravel framework, the application is designed web-based for flexibility of use. The results showed that the implementation of product and inventory applications at the company made goods control more secure while data information was present in real time.